2021
DOI: 10.3390/nu13041201
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Prevents S-Adenosylmethionine-Mediated Improvements in Age-Related Peripheral and Hippocampal Outcomes

Abstract: Background: Age predisposes individuals to a myriad of disorders involving inflammation; this includes stress-related neuropsychiatric disorders such as depression and anxiety, and neurodegenerative diseases. Obesity can further exacerbate these effects in the brain. We investigated whether an inexpensive dietary supplement, s-adenosylmethionine (SAMe), could improve age- and/or obesity-related inflammatory and affective measures in the hippocampus. Methods: Mice were placed on their diets at six weeks of age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Obesity is one of the major conditions that gives rise to a myriad of comorbid, inflammation driven, chronic diseases particularly as aging progresses [ 62 , 63 ]. Table 2 illustrates examples of 43 comorbid NCDs for obesity [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. The obese population carries one of the highest risks for multiple future NCDs of any disease-burdened cohort.…”
Section: Two High-impact Examples Of Ncdsmentioning
confidence: 99%
“…Obesity is one of the major conditions that gives rise to a myriad of comorbid, inflammation driven, chronic diseases particularly as aging progresses [ 62 , 63 ]. Table 2 illustrates examples of 43 comorbid NCDs for obesity [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. The obese population carries one of the highest risks for multiple future NCDs of any disease-burdened cohort.…”
Section: Two High-impact Examples Of Ncdsmentioning
confidence: 99%
“…Such microglial plasticity is also supported by a time-course study performed in mice fed HFD for 1-28 days, in which hypothalamic microglia express different markers at different times, with an early increase in CD86 expression at 3 days on HFD, followed by a decrease in this pro-inflammatory marker concomitant with the overexpression of CD206 [175] and arginase-1 [176] at 7 days on HFD, and a final overexpression of MHC-II after 28 days on HFD [175]. Consistent with the upregulation of some microglial markers, many studies have reported that microglia from HFD-fed rodents display an amoeboid morphology with thickened processes in several brain regions [147,150,152,153,157,165,167,168,177]. Conversely, one study in which rats were exposed to free-choice high-fat high-sugar diet did not find morphological changes in microglia neither in the cortex nor in the hippocampus [178].…”
Section: High-fat Diet-induced Metabolic Diseasementioning
confidence: 77%